Uncovering the Determinants of Birth Weight: An Investigation on Pregnant Women in Makassar City - Arief, Ria Qadariah; Sarih , Karmila; Mahmud , Nur Ulmy (Diversity: Disease Preventive of Research Integrity, 2023)
Birth weight is an essential indicator in assessing a baby's health and a factor that affects the baby's long-term health. This study aimed to determine the relationship between the Body Mass Index (BMI), Hemoglobin levels, and Blood Pressure of mothers during pregnancy and to birth weight of the baby. The study used a cross-sectional survey of a group of mothers who gave birth in Makassar. The data on mothers during pregnancy was the maternal history recorded in the mother and Child Health Book (KIA). And the data on the birth weight of the baby was also from the KIA book with the support of secondary data from the Community Health Center and Midwife. The results showed that 41.7% of the low-birth-weight babies had mothers who experienced underweight during pregnancy, 83.3% of the low-birth-weight babies had mothers who experienced Anemia during pregnancy, and 66.7% of the low-birth-weight babies had mothers who experienced hypertension during pregnancy. There was a significant and close relationship between the mother's BMI, Hemoglobin levels, and Blood Pressure to the baby's birth weight. There was a meaningful relationship between the mother's Body Mass Index, Anemia, and Hypertension during pregnancy to low birth weight. Therefore, it is important to maintain a good quality of nutrition for mothers both before and during pregnancy, following Islamic teachings that Allah SWT has decreed for every pregnant woman a thousand good deeds every day and erases a thousand misdeeds as motivation to remain strong throughout the pregnancy process.